IMPLEMENTASI KEBIJAKAN DISIPLIN DAN PENEGAKAN HUKUM PROTOKOL KESEHATAN SEBAGAI UPAYA PENCEGAHAN DAN PENGENDALIAN COVID-19 DI KECAMATAN JOMBANG KABUPATEN JOMBANG - Evi Wahyuni; Diana Hertati (Journal Publicuho, 2021)
Jombang Regent Regulation Number 57of 2020 concerning Implementation of the Discipline , and Law Enforcement of Health Protocols as Efforts to Prevent and Control COVID-19 is a regulation passed by the Regent of Jombang as an effort to control the spread of COVID-19 in Jombang Regency. The purpose of this research to describe and analyze the implementation of disciplinary policies and law enforcement of health protocols as an effort to prevent and control COVID-19 in Jombang District, Jombang Regency. The theory used in this research is the implementation model theory by Edward III. The type of this research used descriptive qualitative. The results of this study indicate that: (1) Communication has been implemented but still not done well, especially on consistency; (2) Resources are well implemented; (3) The disposition has been implemented very well, especially in cognition, direction and response of the executor, as well as the intensity of the response or implementation response; (4) The bureaucratics tructure has not been well implemented because it does not have a written flow of officers or fragmentation of responsibility in writing between the threes's health protocol law enforcement agencies